Wheat straw decomposition stage has little effect on the removal of inorganic N and P from wastewater leached through sand-straw mixes. Issue 26 (22nd November 2020) - Le, Thi Huong Xuan; Mosley, Luke; Marschner, Petra
ABSTRACT: Wheat straw amendment to sandy soil can remove nitrogen (N) and phosphorus (P) from wastewater but it is unclear whether prior decomposition affects removal. Sand mixed with finely ground wheat straw at 12.5 g straw kg −1 was placed in leaching columns. Wastewater was added either immediately after mixing with straw (fresh straw) or after the sand-straw mix had been incubated moist for 7 or 14 days (7D or 14D straw). Sand alone was considered as control. Leaching was carried out 4, 8 or 16 days after addition of wastewater and inorganic N and P were analysed after leaching in both leachate and sand. In the amended treatments, nitrate and available P in the sand-straw mix were not detectable throughout the experiment. On day 16, inorganic N in the sand-straw mix was highest in fresh straw where it was three-fold higher than in 14D straw and 30% higher than in sand alone and 7D straw on day 16. Straw decomposition stage had no consistent effect on microbial biomass N and P. Released CO2 was lower in 14D straw than in fresh straw and 7D straw. With straw amendment, > 95% of inorganic N added with wastewater was removed compared to 40–50% with sand alone. Inorganic P leaching was reduced by about 30% compared to sand alone on day 16. In conclusion, wheat straw addition reduced leaching of N compared to sand alone, but the decomposition stage of the straw had little effect on the removal of N and P from wastewater. GRAPHICAL ABSTRACT: UF0001